2022
DOI: 10.3390/photonics9060406
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and Gamma Spectroscopy of Phosphate Glass Doped with Nd3+/Yb3+ and Their Multifunctional Applications

Abstract: A new glass with a composition of 40P2O5-30ZnO-20LiCl-10BaF2 (in mol%), doped with 3.5Nd2O3-3.5Yb2O3, was fabricated by the quenching melt technique. The luminescence (PL) and gamma spectroscopy of the glass were investigated systematically. The spectroscopic parameters of the prepared glass, such as the optical energy gap, Judd–Ofelt parameters Ωk (where k = 2, 4 and 6), lifetimes and branching ratio of the Nd3+/Yb3+ level, were evaluated. Moreover, the shielding parameters, such as the linear and mass attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The results obtained showed that the value of E opt is 4.72 ± 0.01 eV for PZBLPr glass. It has the highest value of E opt compared to tellurite glass and other glass doped with the Nd 3+ /Yb 3+ system that have been reported previously [ 24 , 25 , 26 , 27 ]. This is due to the presence of Pr 3+ ions, which leads to an increase in both the width of the localized state in the forbidden gap and the density of electrons, therefore, increasing the probability of electronic transition from the valence band to the conduction band.…”
Section: Resultsmentioning
confidence: 76%
“…The results obtained showed that the value of E opt is 4.72 ± 0.01 eV for PZBLPr glass. It has the highest value of E opt compared to tellurite glass and other glass doped with the Nd 3+ /Yb 3+ system that have been reported previously [ 24 , 25 , 26 , 27 ]. This is due to the presence of Pr 3+ ions, which leads to an increase in both the width of the localized state in the forbidden gap and the density of electrons, therefore, increasing the probability of electronic transition from the valence band to the conduction band.…”
Section: Resultsmentioning
confidence: 76%
“… where B is a constant known as the band tailing parameter, r, which depends on the type of mechanism transition (r = 2) associated with the allowed indirect transitions [ 30 ] A graph was plotted for versus to determine the indirect optical band gap, E opt , as shown in Figure 4 . The calculated values of the indirect optical band gap, , can be obtained by the extrapolation of the linear range of the curve with a linear axis at (Y-axis = 0), which represents the photon energy [ 31 ] and the value of E opt for the prepared glass, as evaluated in Table 3 . In the BBTTRE glass system, the formation of TeO 4 caused oxygen anions to be tightly bound to the host materials; thus, the E opt increased with a decrease in the number of NBO [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The calculated values of the indirect optical band gap, , can be obtained by the extrapolation of the linear range of the curve with a linear axis at (Y-axis = 0), which represents the photon energy [ 31 ] and the value of E opt for the prepared glass, as evaluated in Table 3 . In the BBTTRE glass system, the formation of TeO 4 caused oxygen anions to be tightly bound to the host materials; thus, the E opt increased with a decrease in the number of NBO [ 31 ]. The value of E opt depends on the structure of the prepared glass TBBT modified by 3RE 2 O 3 in mol , where RE is La, Ce, Sm, Er, or Yb.…”
Section: Resultsmentioning
confidence: 99%
“…9 When light travels through glass, the intensity is reduced because it is partially absorbed; therefore, translucency decreases by light scattering. 27,28 When comparing the two presintered blocks, IPS e.max CAD presented higher glass content and displayed higher translucency values (groups 6 and 7) than Amber Mill (groups 4 and 5). The fully sintered Straumann n!ce is a lithium disilicate-strengthened lithium aluminosilicate, 29 whereas the other brands do not have aluminosilicate; therefore, their effects on light translucency need to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The fully sintered Straumann n!ce contains the lowest glass amount with 19.4%, followed by the traditional presintered IPS e.max CAD with 29.7%, and the presintered Amber Mill contains the highest amount with 39.9% 9 . When light travels through glass, the intensity is reduced because it is partially absorbed; therefore, translucency decreases by light scattering 27,28 . When comparing the two presintered blocks, IPS e.max CAD presented higher glass content and displayed higher translucency values (groups 6 and 7) than Amber Mill (groups 4 and 5).…”
Section: Discussionmentioning
confidence: 99%